Synthesis of a Novel Low-Component Programmable Sinusoidal Oscillator - Muhammad Taher Abuelma'atti; Sa'ad Muhammad Al-Shahrani (Active and Passive Electronic Components)
A novel circuit is presented for realizing a sinusoidal oscillator. The proposed circuit, developed through a true synthesis approach, uses one current-feedback operational amplifier (CFOA), one operational transconductance amplifier (OTA), three grounded capacitors and one floating resistor. The proposed circuit enjoys several attractive features. Practical results, in excellent agreement with the presented theory, are included.